A hard pill to swallow: a qualitative study of women's experiences of adjuvant endocrine therapy for breast cancer. Issue 6 (12th June 2014) - Harrow, Alison; Dryden, Ruth; McCowan, Colin; Radley, Andrew; Parsons, Mark; Thompson, Alastair M; Wells, Mary
Abstract : Objective: To explore women's experiences of taking adjuvant endocrine therapy as a treatment for breast cancer and how their beliefs about the purpose of the medication, side effects experienced and interactions with health professionals might influence adherence. Design: Qualitative study using semistructured, one-to-one interviews. Setting: 2 hospitals from a single health board in Scotland. Participants: 30 women who had been prescribed tamoxifen or aromatase inhibitors (anastrozole or letrozole) and had been taking this medication for 1–5 years. Results: Women clearly wished to take their adjuvant endocrine therapy medication as prescribed, believing that it offered them protection against breast cancer recurrence. However, some women missed tablets and did not recognise that this could reduce the efficacy of the treatment. Women did not perceive that healthcare professionals were routinely or systematically monitoring their adherence. Side effects were common and impacted greatly on the women's quality of life but did not always cause women to stop taking their medication, or to seek advice about reducing the side effects they experienced. Few were offered the opportunity to discuss the impact of side effects or the potential options available. Conclusions: Although most women in this study took adjuvant endocrine therapy as prescribed, many endured a range of side effects, often without seeking help. Advice, support and monitoring for adherence are not routinely offered in conventional follow-up settings. Women deserve more opportunity to discuss the pros, cons and impact of long-term adjuvant endocrine therapy. New service models are needed to support adherence, enhance quality of life and ultimately improve survival. These should ideally be community based, in order to promote self-management in the longer term.